Prenatal Distress pada Ibu Hamil Usia Remaja dan Faktor yang Memengaruhinya - Ike Puspasari Ayu; Aminah (Faletehan Health Journal, 2025)
Pregnancy during adolescence is vulnerable to psychosocial problems, including prenatal distress, which can have adverse effects on the well-being of the mother and fetus in both the short and long term. This study aims to identify the prevalence of prenatal distress among adolescent pregnant women and its determinants. A descriptive-analytical study with a cross-sectional design was conducted among 242 adolescent pregnant women in Serang City, selected using consecutive sampling. Instruments included a socio-demographic questionnaire, PTSD Symptom Scale (PSS), Multidimensional scale of perceived social support (MSPSS), London Measure of Unplanned Pregnancy Instrument (LMUP), Marital Adjustment Test (MAT), and Prenatal distress Questionnaire (PDQ). Data were analyzed multivariately using logistic regression. Most respondents (66.5%) experienced prenatal distress. Significant determinants included gravida status, social support, pregnancy planning, and marital satisfaction. Logistic regression showed low social support (OR=8.77), marital dissatisfaction (OR=5.40), unplanned pregnancy (OR=3.80), and primigravida (OR=2.61) as the four main predictors. Supports from various parties are needed to overcome prenatal distress in pregnant adolescents, so that mothers are better prepared for their pregnancies.